Analisis Yuridis Wanprestasi Perjanjian Waralaba Menurut Peraturan Pemerintah Nomor 42 Tahun 2007 Tentang Waralaba (Studi Kasus Perjanjian Waralaba PT X Dengan Mitra Di Surabaya) - Dinadi, Naura Aisyla; Wahyudi, Eko (Peneliti.net, 2024)
This research aims to analyze legal protection for franchisee in implementing the franchise agreement. A franchise is an agreement between two parties where the parties are the giver and recipient of the franchise. A franchisor is